1990
DOI: 10.2307/1242345
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Empirical Advantages of Truncated Count Data Estimators for Analysis of Deer Hunting in California

Abstract: Truncated Poisson and truncated negative binomial count data models, as well as standard count data models, OLS, nonlinear normal, and truncated nonlinear normal MLE were used to estimate demand for deer hunting in California. The truncated count data estimators and their properties are reviewed. A large sample (N = 2223) allowed random segmenting of the data into specification, estimation, and out‐of‐sample prediction portions. Statistics of interest are therefore unbiased by the specification search, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
223
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(234 citation statements)
references
References 7 publications
10
223
0
1
Order By: Relevance
“…Trips are a count data variable, which is usually Poisson distributed, meaning that a small number of people visit quite frequently while most visit rarely. However, since survey data almost never meet Poisson's stringent requirement of the mean being equal to the variance, a Poisson regression produces biased and inconsistent coefficients (Creel & Loomis, 1990;Grogger & Carson, 1991). The mean equals variance requirement of Poisson is relaxed in the negative binomial regression by including a parameter alpha to capture the degree of over dispersal in the sample (Martínez-Espiñeira & Amoaka-Tuffour, 2008).…”
Section: B Modelling With Zero Truncated Endogenously Stratified Counmentioning
confidence: 99%
See 3 more Smart Citations
“…Trips are a count data variable, which is usually Poisson distributed, meaning that a small number of people visit quite frequently while most visit rarely. However, since survey data almost never meet Poisson's stringent requirement of the mean being equal to the variance, a Poisson regression produces biased and inconsistent coefficients (Creel & Loomis, 1990;Grogger & Carson, 1991). The mean equals variance requirement of Poisson is relaxed in the negative binomial regression by including a parameter alpha to capture the degree of over dispersal in the sample (Martínez-Espiñeira & Amoaka-Tuffour, 2008).…”
Section: B Modelling With Zero Truncated Endogenously Stratified Counmentioning
confidence: 99%
“…In practice, the price of substitute sites was not universally included in the literature. Some studies omitted it for good reason; for example, once a license for hunting at a specific site had been purchased, the site no longer had relevant substitutes (Creel & Loomis, 1990). Other studies omitted the price of substitute sites for convenience (Rosenthal, 1987;Common et al, 1997;Garrod & Willis, 1999;Liston-Heyes & Heyes, 1999).…”
Section: Trip Demand Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Results suggested that the annual net present value for camping at this park alone was nearly $40 million. Other recent analyses include valuing hiking in National Forests in Colorado and Montana (Hesseln et al, 2004), canoeing in Canada (Hellerstein, 1991), hunting in California (Creel & Loomis, 1990), Chinook Salmon sport fishing in Alaska (Layman et al, 1996), and ecotourism and wildlife viewing in Costa Rica, and Kenya (Menkhaus & Lober, 1996;Navrud & Mungatana, 1994). This method could similarly be employed to value the flow of recreation services from the Salton Sea.…”
Section: Travel Cost Methodsmentioning
confidence: 99%